2011
DOI: 10.1590/s0102-76382011000200016
|View full text |Cite
|
Sign up to set email alerts
|

Mortality within the endovascular treatment in Stanford type B aortic dissections

Abstract: dor persistente apesar da terapia médica, sinais de isquemia distal do membro, sinais de ruptura da aorta, progressão da dilatação do aneurisma da aorta descendente, durante o seguimento (definida como um diâmetro > 5 cm) e descendente da aorta torácica de 40 mm ou mais de diâmetro no início da dissecção aórtica. Os dados foram analisados estatisticamente considerados erro alfa de 5%. As variáveis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
(25 reference statements)
3
9
0
1
Order By: Relevance
“…Aortic enlargement is associated with rupture of the aorta in patients with Stanford B AAD and is one of the main reasons for late death. In our study, four of nine (44.4%) patients died of aortic‐related complications, which was consistent with those of previous studies …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Aortic enlargement is associated with rupture of the aorta in patients with Stanford B AAD and is one of the main reasons for late death. In our study, four of nine (44.4%) patients died of aortic‐related complications, which was consistent with those of previous studies …”
Section: Discussionsupporting
confidence: 93%
“…In this study, the late mortality was 16.07%, at the 52‐month average follow‐up; the actuarial survival was similar between the two groups in the trial from the Massachusetts General Hospital . The five‐year survival was 68%.…”
Section: Discussionmentioning
confidence: 48%
“…Fioranelli et al [ 26 ] reported that the presence of reentry thoracic aorta was correlated with the patency of the false lumen in the postoperative follow-up and agreed with the findings of Kato et al. [ 23 ] ; Shimono et al.…”
Section: Introductionsupporting
confidence: 79%
“…Aortic rupture is the primary cause of aortic-related death following TEVAR and comprises 50% to 100% of all causes of death (12,29,30). The aortic-related deaths in our series were also mostly due to aortic rupture (24 of 27; 88.9%).…”
Section: Instead-xl Trial Showed Tevar In Addition Tomentioning
confidence: 61%